Antimicrobials and antimicrobial resistance - Panagiotopoulou, Dimitra (2020)
The discovery of penicillin has revolutionised the field of modern medicine. However, misuse and overconsumption of antibiotics have led to the rise of antimicrobial resistance (AMR). The prevalence of AMR and the lack of novel antimicrobial therapies threaten to bring society back to the pre-antibiotic era. Therefore, it is imperative to develop state-of-the-art antimicrobial strategies which can be achieved by expanding our understanding of the biology of pathogenic bacteria. This report details three AMR research projects with the first focussing on the control of the three Escherichia coli peptidoglycan amidases by two new regulatory proteins, YraP and NlpI. Direct interactions between YraP and amidases were investigated by employing pull-down assays however the results were inconclusive. Also, the effect of NlpI on the hydrolytic activity of amidases in vitro was explored, detecting no change in the activity of AmiA amidase. The second project examined the methodology of Next Generation Sequencing (NGS) data analysis. For this purpose, publicly available raw sequence data from a publication on Pseudomonas aeruginosa global clone ST395 were used. Overall, the computational pipeline used here produced different results to that of the publication which shows the dependence of the outcome on the choice of bioinformatic programmes. In the last chapter, a new small non-coding RNA, the PqsX, is studied along with its potential roles in the regulation of the pqs Quorum Sensing (QS) system of P. aeruginosa. The pqs system controls the expression of virulence factors which makes it a significant target for the development of antivirulent therapies.